2014
DOI: 10.1120/jacmp.v15i3.4509
|View full text |Cite
|
Sign up to set email alerts
|

A patient‐based dosimetric study of intracavitary and interstitial brachytherapy in advanced stage carcinoma of the cervix

Abstract: Intracavitary brachytherapy (ICBT) and interstitial brachytherapy (IB) techniques are commonly practiced for treating carcinoma of the cervix, either alone or in combination with external beam radiotherapy. Both these brachytherapy techniques have their own advantages and limitations in terms of tumor coverage and normal tissue sparing. Limited studies have been reported comparing the dosimetric features of these two techniques, especially from a single institution. We carried out a prospective clinical dosime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…The TRAK values are also similar in both the cases as shown in Table 1. These values (4.91 and 4.93 mGy) are close to the value (5.1 mGy) reported by Bansal et al (2014) [15]. The tilt angle of the intrauterine tandem towards left or right side with respect to the patient midline was also noted to its effect on dose distribution.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The TRAK values are also similar in both the cases as shown in Table 1. These values (4.91 and 4.93 mGy) are close to the value (5.1 mGy) reported by Bansal et al (2014) [15]. The tilt angle of the intrauterine tandem towards left or right side with respect to the patient midline was also noted to its effect on dose distribution.…”
Section: Resultssupporting
confidence: 88%
“…The thickness value for the fixed applicator is similar to the one quoted by Bansal et al, i.e. 4.45 cm [15]. The thickness difference in the two types of geometries could translate into higher rectum/bladder dose but was not found to be so for all the cases.…”
Section: Resultssupporting
confidence: 77%
“…Nevertheless, a biological correlation between HR-CTV hotspots and local control for cervical cancer is unknown. In our study, we could achieve median HR-CTV hotspots of greater than 62% (V 150 ) and 39% (V 200 ) by volume-based planning and were comparable to the data reported by other studies [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…A study by Bansal et al. 18 showed that interstitial needles (number ranged from 18 to 26) combined with an intrauterine tandem resulted in significantly higher doses to 2 cm 3 of the bladder than intracavitary alone (Fletcher tandem and ovoids), with comparable doses to 2 cm 3 for the rectum and sigmoid. It supported our study to use a lesser number of needles to reduce the dose to the bladder 2 cm 3 , where they used 18–26 needles and this study tried to reduce the needles number to 6–10.…”
Section: Discussionmentioning
confidence: 99%
“…There were only 42 (17.9%) replans with bladder 2 cm 3 being failed among 234 replans from nine configurations to achieve the dose coverage compared to the full‐loading. A study by Bansal et al 18 . showed that interstitial needles (number ranged from 18 to 26) combined with an intrauterine tandem resulted in significantly higher doses to 2 cm 3 of the bladder than intracavitary alone (Fletcher tandem and ovoids), with comparable doses to 2 cm 3 for the rectum and sigmoid.…”
Section: Discussionmentioning
confidence: 99%